Development of land rental markets and agricultural productivity growth: the case of northern Ethiopia - Benin, Samuel; Ahmed, Mohamed Hassan; Pender, John L.; Ehui, Simeon K. (Oxford University Press, 2005)
Short-term land leases have an important role to play for efficient land management and agricultural development, especially when land sales and mortgages are prohibited and markets for other factor inputs are imperfect or missing. This study utilises data from the highlands of northern Ethiopia to examine the evolution since 1991 of land rental markets, factors contributing to the changes and impact of the changes on land productivity growth. Use of fixed-rent lease and 50–50 sharecropping arrangements have increased substantially and are the dominant forms of land rental. The major factors contributing to the increase in use of land rental arrangements include change in the production environment, change in access to credit, commercialisation of cereal production, change in human capital and change in tenure security. The increase in use of land rental markets has had a positive impact on change in average cereal yields and the impacts associated with increases in use of fixed-rent leases or sharecropping arrangements are not statistically different. Together, the results suggest that land tenure arrangements are indeed dynamic and have evolved in a manner that has eliminated any Marshallian inefficiencies associated with share tenancy.